Penatalaksanaan Arthritis Gout pada Perempuan Usia 59 Tahun dengan Pendekatan Kedokteran Keluarga - Indah Anita Dewi,; Reni Zuraida (Majority, 2021)
Gout is a progressive disease due to deposition of monosodium urate (MSU) crystals in joints, kidneys, and other connective tissues as a result of chronically elevated serum uric acid levels above normal. The prevalence of hyperuricemia and gout in Indonesia is higher than other Asian countries. Dietary factors with excessive puring consumption are one of the risks factor of gout. Therefore, in an effort to treat disease, the role of the family is needed to achieve good therapeutic goals. The purpose of this study is to identify internal and external risk factors in patients, apply a holistic and comprehensive family doctor approach, and perform management based on Evidence Based Medicine that is familyapproach and patient-centered. A 59-year-old female patient came with complaints of pain in both knees. Initially the pain was only felt in the patient's right knee, a few weeks later the patient began to feel pain in the patient's left knee. Complaints are accompanied by swelling, redness and heat. The patient has been diagnosed with gout since 2 years ago. Patients do not routinely control their illness and only seek treatment if complaints interfere with their activities. Internal risk factors are the patient does not know the target of normal uric acid levels, what types of food can cause uric acid levels, the pattern of curative treatment, and the patient does not like to exercise. The external risk to the patient is that the family does not know how to prepare food according to the patient's diet and appropriate physical activity. Intervention was carried out regarding the type of food and appropriate physical activity and the importance of routinely checking uric acid in 3 home visits. After the evaluation, the knowledge of the patient and family about the disease were increased.